Evaluation of tritium release curve in primary coolant of research reactors (Physical Sciences and Technology, 2018)
Increase of tritium concentration in the primary coolant for the research and testing reactors during reactoroperation had been reported. To clarify the tritium sources, a curve of the tritium release rate into the primarycoolant for the JMTR and the JRR-3M are evaluated. It is also observed that the amount of released tritium islower in the case of new beryllium components installation, and increases with the reactor operating cycle.These results show the beryllium components in core strongly affect to the tritium release into the primarycoolant. As a result, the tritium release rate is related with produced 6Li by (n,α) reaction from 9Be, andevaluation results of tritium release curve are shown as the dominant source of tritium release into the primarycoolant for the JMTR and the JRR-3M are beryllium components. Scattering of the tritium release rate withirradiation time were observed, and this phenomena in the JMTR occurred in earlier time than that of the JRR-3M.